RV-pulmonary arterial coupling predicts outcome in patients referred for pulmonary hypertension. Issue 1 (11th September 2014) - Vanderpool, Rebecca R; Pinsky, Michael R; Naeije, Robert; Deible, Christopher; Kosaraju, Vijaya; Bunner, Cheryl; Mathier, Michael A; Lacomis, Joan; Champion, Hunter C; Simon, Marc A
Abstract : Objective: Prognosis in pulmonary hypertension (PH) is largely determined by RV function. However, uncertainty remains about what metrics of RV function might be most clinically relevant. The purpose of this study was to assess the clinical relevance of metrics of RV functional adaptation to increased afterload. Methods: Patients referred for PH underwent right heart catheterisation and RV volumetric assessment within 48 h. A RV maximum pressure (Pmax) was calculated from the RV pressure curve. The adequacy of RV systolic functional adaptation to increased afterload was estimated either by a stroke volume (SV)/end-systolic volume (ESV) ratio, a Pmax/mean pulmonary artery pressure (mPAP) ratio, or by EF (RVEF). Diastolic function of the RV was estimated by a diastolic elastance coefficient β. Survival analysis was via Cox proportional HR, and Kaplan–Meier with the primary outcome of time to death or lung transplant. Results: Patients (n=50; age 58±13 yrs) covered a range of mPAP (13–79 mm Hg) with an average RVEF of 39±17% and ESV of 143±89 mL. Average estimates of the ratio of end-systolic ventricular to arterial elastance were 0.79±0.67 (SV/ESV) and 2.3±0.65 (Pmax/mPAP-1). Transplantation-free survival was predicted by right atrial pressure, mPAP, pulmonary vascular resistance, β, SV, ESV, SV/ESV and RVEF, but after controlling for right atrial pressure, mPAP, and SV, SV/ESV was the only independent predictor. Conclusions: The adequacy of RV functional adaptation to afterload predicts survival in patients referred for PH. Whether this can simply be evaluated using RV volumetric imaging will require additional confirmation.